Long‐term outcomes of patients undergoing simultaneous liver transplantation and sleeve gastrectomy. Issue 2 (14th May 2018) - Zamora‐Valdes, Daniel; Watt, Kymberly D.; Kellogg, Todd A.; Poterucha, John J.; Di Cecco, Sara R.; Francisco‐Ziller, Nicki M.; Taner, Timucin; Rosen, Charles B.; Heimbach, Julie K.
Abstract : Obesity is increasingly common before and after liver transplantation (LT), yet optimal management remains unclear. The aim of this study was to analyze the long‐term outcomes for obese patients undergoing LT, including a noninvasive weight loss program and combined LT and sleeve gastrectomy (SG). Since 2006, all patients referred for LT with a body mass index (BMI) ≥35 kg/m 2 were enrolled. Patients who achieved weight loss (BMI <35) underwent LT alone, and those who did not underwent simultaneous LT + SG. Analysis of long‐term outcomes for patients ≥3 years posttransplant was performed. Since 2006, there were 36 in the weight loss intervention (LT cohort) and 13 in the LT + SG cohort with >3 years of follow‐up, whereas overall, a total of 29 patients underwent LT + SG. Patients in the LT cohort had less severe obesity at enrollment (40.0 ± 2.7 vs. LT + SG cohort 46.0 ± 4.5; P < 0.001). In the LT cohort, 83.3% (30 of 36) achieved >10% loss in total body weight (TBW) pre‐LT. Three years posttransplant, 29.4% of patients in the LT cohort maintained >10% loss in TBW, whereas 100% of the LT + SG patients did ( P < 0.001). Patients who underwent LT + SG maintained a significantly higher percentage of total body weight loss after 3 years of follow‐up (LT cohort 3.9 ± 13.3% vs. LT + S G cohort 34.8 ± 17.3%; P < 0.001). Patients in the LT + SG also had a lower prevalence of hypertension, insulin resistance, and hepatic steatosis and required fewer antihypertensive medications and lipid agents at last follow‐up. Conclusion : Whereas weight loss before transplantation was achieved by obese patients, weight regain was common in the LT cohort. Combined LT + SG resulted in more effective and more durable weight loss, as well as fewer metabolic complications at last follow‐up. (Hepatology 2018).